Antimicrobial stewardship education in US colleges and schools of pharmacy. (28th May 2018) - Kufel, Wesley D; Jeffres, Meghan N; MacDougall, Conan; Cho, Jonathan C; Marx, Ashley H; Williams, Dennis M
Abstract: Background: Pharmacists are key members of antimicrobial stewardship (AS) teams. It is unknown if and how US colleges and schools of pharmacy incorporate AS into their Doctor of Pharmacy (PharmD) curricula. Methods: This study was a cross-sectional, multicentre, electronic survey distributed to infectious diseases faculty or department chairs of 137 accredited and candidate-status PharmD programmes. Results: One hundred and sixteen programmes participated, representing an 84.7% response rate. AS education was integrated into the required didactic, elective didactic and experiential education components of the curricula in 79 (68.1%), 43 (37.1%) and 97 (83.6%) PharmD programmes, respectively. The most common AS topics in required and elective didactic curricula were AS definitions, principles and purpose (98.7% and 86.0%) and the pharmacist's role in AS (93.7% and 83.7%). In the required and elective didactic curricula, lecture (93.7% and 86.0%) and case-based instruction (57.0% and 83.7%) were the most common instructional methods. For experiential education, the pharmacist's role in AS (96.9%), de-escalation of antimicrobials (96.9%) and antimicrobial dose optimization (95.9%) were the most common AS topics. PharmD programmes employing a faculty member who specializes in AS were more likely to offer AS experiential education than programmes without AS faculty (88.1% versus 71.9%, P  =   0.049). Conclusions: Integration of AS education in US PharmD curricula is variable and there are considerable differences in the AS activities and topics delivered. PharmD programmes should attempt to expose students to AS education to prepare future pharmacists for AS practice. Efforts should be made to incorporate interprofessional collaboration into AS education.